The impact of moisture on the milling behavior of different biomasses - Williams, Orla; Eastwick, Carol; Lester, Edward; Giddings, Donald; Byrne, Norman (2014)
The aim of this study was to examine the impact of moisture content on the milling behaviour of four different biomasses commonly used in the power sector and characterise their milling behaviour in a laboratory scale planetary ball mill. As received (raw) and dried wood pellets, eucalyptus pellets, olive pellets, and Spanish olive cake were milled for the same milling conditions, and then characterised by energy consumption, particle size, and thermal characterisation. The study found that dry samples have higher energy consumption than raw samples in a laboratory scale planetary ball mill. Drying had varying impacts on the particle size distributions of the samples, with olive cake showing a 60% reduction in mean geometric diameter, while wood and eucalyptus pellets only showed a 15% and 18% reduction respectively. Moisture acts an inhibitor to milling performance, and increased moisture makes biomass more impact resistant, thus reducing ball momentum and resulting in lower energy consumption in the mill.